Genes of cellular components of morphogenesis in porcine oocytes before and after IVM - Budna, Joanna; Bryja, Artur; Celichowski, Piotr; Kahan, Rotem; Kranc, Wiesława; Ciesiółka, Sylwia; Rybska, Marta; Borys, Sylwia; Jeseta, Michal; Bukowska, Dorota; Antosik, Paweł; Brüssow, Klaus P; et al. (Reproduction (Cambridge, England), 2017)
Proper oocyte maturation in mammals produces an oocyte capable of monospermic fertilization and embryo preimplantation. The cumulus-oocyte complexes (COCs), surrounding an oocyte, play a significant role in oocyte maturation. During this process, when the COCs undergo cumulus expansion wherein tightly compact cumulus cells (CCs) form a dispersed structure, permanent biochemical and molecular modifications occur in the maturing oocytes, indicating that the gene expression between immature and mature oocytes differs significantly. This study focuses on the genes responsible for the cellular components of morphogenesis within the developing oocyte. Brilliant cresyl blue (BCB) was used to determine the developmental capability of porcine oocytes. The immature oocytes (GV stage) were compared with matured oocytes (MII stage), using microarray and qRT-PCR analysis to track changes in the genetic expression profile of transcriptome genes. The data showed substantial upregulation of genes influencing oocyte's morphology, cellular migration and adhesion, intracellular communication, as well as plasticity of nervous system. Conversely, downregulation involved genes related to microtubule reorganization, regulation of adhesion, proliferation, migration and cell differentiation processes in oocytes. This suggests that most genes recruited in morphogenesis in porcine oocyte in vitro, may have cellular maturational capability, since they have a higher level of expression before the oocyte's matured form. It shows the process of oocyte maturation and developmental capacity is orchestrated by significant cellular modifications during morphogenesis.
Keywords: buněčná diferenciace; IVM techniky; Sus scrofa; Oligonucleotide Array Sequence Analysis; Female; Phenotype; Cell Adhesion; Genotype; zvířata; proliferace buněk; Cells, Cultured; oocyty; Morphogenesis; Gene Expression Regulation, Developmental; morfogeneze; ženské pohlaví; pohyb buněk; fenotyp; kultivované buňky; Cell Proliferation; stanovení celkové genové exprese; Cell Differentiation; transkriptom; Cell Movement; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; In Vitro Oocyte Maturation Techniques; Real-Time Polymerase Chain Reaction; Transcriptome; genotyp; vývojová regulace genové exprese; Animals; buněčná adheze; Gene Expression Profiling; Oocytes; kvantitativní polymerázová řetězová reakce